Phytochemical screening and in-vitro evaluation of antimicrobial activity of invasive species Ageratina adenophora collected from Kathmandu valley, Nepal - Devkota, Anjana; Das, Ritu K. (Scientific World, 2022)
Antimicrobial activity of invasive alien plant species Ageratina adenophora (Sprengel) R. King & H. Robinson was evaluated against six human pathogenic bacteria. The aqueous (distilled water) and alcoholic (methanol) crude extracts from the leaves of the plant were tested against three gram negative bacteria: Escherichia coli (ATCC 25922), Klebsiella pneumoniaea (ATCC 15380) and Proteus mirabilis (ATCC 49132) and three gram positive bacteria: Enterococcus faecalis (ATCC29212) Bacillus subtilis (ATCC6633) and Staphylococcus aureus (ATCC 25923) using disc diffusion method. Different concentrations of plant extracts (5, 10, 15, 20 and 25%) were applied and diameter of zone of inhibition (ZOI) of bacterial growth were recorded. Plant extract in both solvent exhibited pronounced results against tested bacteria. Methanolic extract of plant exhibited good activity against tested bacteria when compared with aqueous extract. The zone of inhibition of bacterial growth increased with increasing concentrations. Phytochemical screening of plant exhibited alkaloids, saponin, tannin and flavonoids and plant sample contains higher amount of alkaloid. The demonstration of activity against all tested organisms had shown that Ageratina adenophora can be used to produce raw materials/substances for further development of diverse antibiotics with broad spectrum of activity.